A three-dimensional finite element analysis of permanent maxillary central incisors in different stages of root development and trauma settings. (August 2021) - Dezzen-Gomide, Ana Cláudia; de Carvalho, Marco Aurélio; Lazari-Carvalho, Priscilla Cardoso; de Oliveira, Helder Fernandes; Cury, Altair A. Del Bel; Yamamoto-Silva, Fernanda Paula; Silva, Brunno Santos de Freitas
Highlights: The trauma direction has different effects on dental tissues. These effects differ depending on the stage of root development. Finite element analysis is a viable alternative to analyze the stresses and deformations resulting from dental trauma in different stages of root formation. Abstract: Background and objectives: Differences in dental maturation may affect the prognosis and clinical management of traumatized teeth. However, evaluation of the outcomes of dental trauma to the tooth and support structures in an in vivo model involves major methodological and ethical implications. Thus, the aim of the present study was to perform a three-dimensional finite element analysis of permanent maxillary central incisors in different stages of root development under different trauma settings. Methods: The study factors included two trauma conditions (B, buccal; I, incisal) on upper permanent central incisors showing three different stages of root development (CR, complete rhizogenesis; IRA; incomplete rhizogenesis in the apical third of the root; and IRM, incomplete rhizogenesis in the middle third of the root) to yield six models. The complete rhizogenesis model was obtained with a cone-beam computed tomography examination of an extracted tooth. The two incomplete rhizogenesis models were modeled on the basis of similar examinations of patients. Trauma was simulated by applying a 300 N static surface to surface load on the incisal edge or perpendicular to the buccal surface of the tooth. The displacement and equivalent von Mises (σvM) stress values were obtained for alveolar bone, periodontal ligament, apical papilla, and dentin for the quantitative analysis. A σvM color-coded scale was used for qualitative analysis. Results: The force direction had a greater influence on the stress than the root-formation stage. Buccal forces resulted in higher stress concentration in the bone and periodontal ligament, especially in B-CR. Lower stress was found on the periodontal ligament as the root formation progressed (decrease of 8% from B-IRA to B-CR and 11% from B-IRM to B-CR). The incomplete rhizogenesis models showed higher σvM stress peak values in dentin in comparison with complete rhizogenesis (increase of 52% from B-CR to B-IRA and 56% from B-CR to B-IRM). Conclusions: Buccal forces yielded greater stress values regardless of the stage of rhizogenesis. Teeth with fully formed roots showed a higher stress concentration in the alveolar bone and periodontal ligament in comparison with immature teeth, with the latter presenting high stresses in the tooth crown.